THE IMPACT OF PROBLEM-BASED LEARNING APPROACH TO SENIOR HIGH SCHOOL STUDENTS' MATHEMATICS CRITICAL THINKING ABILITY - Reviandari Widyatiningtyas; Yaya S. Kusumah; Utari Sumarmo; Jozua Sabandar (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2015)
The study was report the findings of an only post-test control group research design and aims to analyze the influence of problem-based learning approach, school level, and students' prior mathematical ability to student's mathematics critical thinking ability. The research subjects were 140 grade ten senior high school students coming from excellent and moderate school level. The research instruments a set of mathematical critical thinking ability test, and the data were analyzed by using two ways ANOVA and t-test. The research found that the problem-based learning approach has significant impact to the ability of students' mathematics critical thinking in terms of school level and students' prior mathematical abilities. Furthermore. This research also found that there is no interaction between learning approach and school level, and learning approach and students' prior mathematics ability to students' mathematics critical thinking ability.